Overcoming logistic barriers to enable circular supply chains A case study of physical distribution of cascaded biomass - Thrane Ødum, Miri (My University, 2024)
The green transition is increasing the demand for renewable energy based on various sources of biomasses. Energy recovery via cascading of by-product biomasses has great potential for supporting the green transition and is enabled by circular supply chains. However, there is limited empirical research and a current lack of practical knowledge on how to structure such circular supply chains handling i.e. cascaded biomass. In turn, potentially viable circular business models fall short, despite a competitive market. This is problematic since the demand for biomass is high, and regional markets are under pressure to deliver to the demand. The consuming sectors are therefore highly dependent on facilitation of global biomass supply to produce renewable energy sources such as biogas. The study aims to explore how to overcome practical and economical barriers in a supply chain of cascading biomasses with high melting points for biogas production via logistics improvements. Through an exploratory and problem-solving approach, a scenario analysis of a case company's potential standard transport scenario and an alternative transport scenario, was conducted and analyzed according to costs and practical functionality. As the business cases had no prior examples, data was limited and had to be based on estimations and assumptions. This motivated a sensitivity analysis of the alternative solution to provide better understanding of how the business case was impacted by change in parameters. The overall aim was to enable better decision making on uncertain ground regarding the company's potential business cases. The study suggests that cost efficiency should be priority in the supply chain strategy due to current expensive standard solutions and the characteristics of circular offerings. Moreover, suggestions are made on how to overcome practical barriers and reduce costs via incremental changes in a standard logistics solution, based on changes in equipment, modes, and placing key activities where it is considered optimal both in the supply chain and cost wise. However, the focus on reducing costs to enable viability can compromise finding solutions that actually fits the changed requirements and overcome the barriers that circular offerings induce. Instead, sub optimal solutions are developed, with the same problems in a slightly cheaper package. Bundling, strategic partnerships, and sectorial innovation are proposed as three dimensions to focus attention towards. Bundling will enable volumes that can enable more tailor-made solutions for transportation, and together enable establishing solutions outside the standard scope. Strategic partnerships can enable innovation. Many potential solutions are already possible outside the actor’s standard domain, through industrial symbioses and exploitation of resources and facilities of other industrial actors. Radical innovation is dependent on strategic partnerships as well, to optimally design circular supply chains. Large volumes and many actors can leverage together and push innovation. It is crucial to critically challenge the squared, standardized, and conventional logistics sector, and its ability to adapt to new kinds of products. Radical innovation of the fundamental structures of a conventional sector does not happen overnight. But if global transportation of i.e. biomass gradually increases volumes and causes a phase-out of transportation of fossil energy sources, design of circular transport solutions might become more the norm than the exception. Enabling that tipping point might create the opportunity to rethink fundamentals of current logistics structures.
Keywords: Sustainability; Circular Supply chains; Circular Logistics; cascading of biomass; closing the loop; Waste Management; Biogas production